Role of ultrasound in early prediction of severity of dengue infection - Malleshappa, K; Srinivasa, K (Indian Journal of Child Health, 2022)
Background: Dengue has become a major international health problem in recent years. As per the World Health Organization, dengue has shown a 30-fold increase globally over the past five decades, and approximately, 50-100 million new infections are estimated to occur annually in more than 100 endemic countries. Objective: To evaluate the sonographic findings in children with dengue fever (DF) and to determine its role in predicting the severity of the disease. Methods: One hundred and twenty dengue serology-positive cases in the age group of 2 months to 18 years were studied. These children were divided into two groups - mild (dengue hemorrhagic fever [DHF] I-II without shock) and severe dengue (DHF III-IV with shock). Sonographic variables of these cases were studied and compared by applying appropriate statistical analysis. Results: Out of 120 cases, gallbladder wall thickness (83.3%) and pericholecystic edema (81.6%) were the most common sonographical findings. When sonographic variables of mild and severe groups compared, significant statistical difference was noted in variables such as ascites, pleural effusion, and perinephric edema with p=0.0015, p=0.0058, p